Analysis of Training Design Needs for Accounting Vocational Teachers Using Project Based Learning Approach to Achieve Deep Learning: A Systematic Literature Review - Indah Murtini; Eveline Siregar; Robinson Situmorang (Proceeding of the International Conference on Global Education and Learning, 2025)
This study analyzes the need for training design for accounting vocational teachers using Project Based Learning (PjBL) approach to achieve deep learning through systematic literature review. The gap in teachers' competence in implementing PjBL and the limitations of relevant training designs are major problems in vocational education. This research aims to identify trends, gaps, and needs for developing PjBL-based accounting teacher training designs oriented towards achieving deep learning. The systematic literature review method was employed by analyzing 25 articles from Scopus, ScienceDirect, and Google Scholar databases from 2018-2025. The research identified 25 unique articles categorized into three main themes: Deep Learning perspectives (10 articles), Vocational Teacher Training and Development (6 articles), and Project-Based Learning implementation (9 articles). The results show four main trends: (1) increased global adoption of PjBL as an innovative learning method, (2) demands from accounting professional organizations for active learning methods, (3) popularity of deep learning concepts in contemporary educational literature integrated with 21st-century skills, and (4) urgent need for comprehensive teacher training designs. Significant gaps were identified in the limitations of relevant training designs for vocational contexts and lack of systematic training development research. This study concludes that accounting vocational teacher training designs with PjBL approach are urgently needed to bridge the gap between theoretical competence and practical industry applications, with emphasis on achieving holistic deep learning encompassing cognitive, interpersonal, and intrapersonal domains.